The Legality Issue of the Financing Contract at the Sharia Rural Banks (BPRS) and the Solution in Sharia Agreement Law Perspective - Anggraeny, Isdian; Dinnar Rahmadanti, Wardah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2020)
Sharia-based financing institutions are currently experiencing developments in the financial industry. Sharia financing provided by the BPRS is one of the ways that can be used by the community to meet their daily needs or manage their business. The use of financing certainly has the risk of default and execution of collateral which of course will be detrimental to the creditors (BPRS). Various financing problems are generally caused by the financing process that does not pay attention to legal provisions, especially sharia contract law and guarantee law. Taking the theme: "Issues on the Legality of the Financing Contract at BPRS and its solution in the Perspective of Agreement Law", this paper will examine two problems, namely: First, reviewing the validity of the Sharia financing contract at BPRS based on the Sharia Economic Law Compilation; and second, reviewing and finding the efforts that should be made by the BPRS so that the sharia financing contract meets the pillars and conditions of the contract in the Sharia Economic Law Compilation. This study uses a normative juridical research method with a statutory approach method, concepts, and cases. Through this method, the following findings were obtained: First, the problem of sharia financing in BPRS Syariah lies in the non-fulfillment of the Rukun and the terms of the sharia contract in some of its financing contracts which are dominated by carelessness in applying the legal principles of financing and SOPs that have been made. Second, the BPRS and its Customers must pay attention to and understand the elements of the fulfillment of the pillars and terms of the contract in the financing contract against the rules contained in the Sharia Economic Law Compilation.